Pemahaman Tingkat Kepatuhan Mahasiswa Elektro FPTI UPI Bandung terhadap K3 Listrik dalam Kegiatan Praktikum - Pratama, Zikri Sandria; S, Sukisman; Faoz, Muhammad; Raditya, Muhamad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to evaluate the level of understanding and compliance of students regarding electrical Occupational Health and Safety (OHS) principles during practicum activities at the Department of Electrical Engineering Education, FPTI UPI Bandung. A quantitative approach was used, and data were collected through a closed-ended Likert scale questionnaire involving 54 respondents. The results indicate that students generally have a good conceptual understanding of electrical safety, particularly in recognizing risks and the importance of safety protocols. However, weaknesses remain in implementation aspects such as the consistent use of Personal Protective Equipment (PPE) and prior exposure to safety materials. The highest average score was found in the perception of safety importance (mean: 3.69), while the lowest was in PPE usage (mean: 2.80). These findings highlight the need for continuous safety education and consistent application of standard safety procedures. This research provides a foundation for fostering a safety culture in technical education environments.